2015
DOI: 10.1007/s10762-015-0165-5
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Refractive Index and Absorption Coefficient of Congruent and Stoichiometric Lithium Niobate in the Terahertz Range

Abstract: Time domain THz spectroscopy measurements were performed on a series of undoped and Mg-doped congruent lithium niobate crystals with 1.2, 6.1, and 8.4 mol% Mg concentrations and on undoped and Mg-doped stoichiometric lithium niobate crystals with 0.7, 1.5, and 4.2 mol% Mg concentrations with polarization parallel (extraordinary) and perpendicular (ordinary) to the z axis of the crystal at 300 K. The absorption coefficient and refractive index spectra were determined in the THz frequency range from 0.25 to~2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…The results of refractive index and absorption coefficient lower than 0.9 THz at different temperatures were unrevealed, which are essential in the intense THz generation by the tilted pulse front method. Although Unferdorben et al recently reported the measurements by using a THz time-domain spectrometer (THz-TDS) on a series of lithium niobate crystals with parallel surfaces [25], the results of temperature dependence are still lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of refractive index and absorption coefficient lower than 0.9 THz at different temperatures were unrevealed, which are essential in the intense THz generation by the tilted pulse front method. Although Unferdorben et al recently reported the measurements by using a THz time-domain spectrometer (THz-TDS) on a series of lithium niobate crystals with parallel surfaces [25], the results of temperature dependence are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature was varied from 300 K to 50 K in the THz-TDS system. We measured the refractive index and absorption coefficient for both ordinary (THz polarization parallel to the X-axis of lithium niobate crystal) and extraordinary polarizations (THz polarization parallel to the Z-axis) [25] at different crystal temperatures. Based on the temperature dependent measurements, we find that cryogenic cooling not only decreases the absorption for THz waves but also decreases the refractive index of the crystal in the THz frequency range, which makes the optimization conditions for low temperature and room temperature not the same.…”
Section: Introductionmentioning
confidence: 99%
“…In ISRS excitation, the excited volume is the sample thickness of 500 µm. On the other hand, the THz radiation is strongly absorbed leading to an excitation depth (and therefore excited volume) of only ~ 60 µm [23]. The bottom-axis shows the 800 nm fluence for the ISRS traces, and the upper-axis shows the peak-topeak field strength for THz excitation, and the inset is a zoomed-in look at the lower amplitude region.…”
mentioning
confidence: 99%
“…LiNbO 3 has negative birefringence and smaller extraordinary absorption compared to ordinary both in the optical and in the THz ranges [16,17].…”
Section: Resultsmentioning
confidence: 99%